Updated distribution and morphological variation of the genus Pseudanos in the Río de la Plata basin (Characiformes: Anostomidae) - Vanegas Rios, James Anyelo (2024)
Pseudanos is a fish genus with cis-Andean distribution in South America. Pseudanos trimaculatus is originally known from the Amazon and Orinoco basins. Three decades ago, a few specimens collected in the Río de la Plata basin were identified as P. trimaculatus, what remained to be confirmed and understood. The aim of this contribution is to analyze these specimens. Consequently, the morphological variation of P. trimaculatus is discussed and updated. Morphometric and meristic data were taken from the specimens and compared with those of the type and non-type specimens of the species. Multivariate analyses of the size-corrected measurements were used to explore the morphological variation. Size-corrected PCA revealed that the specimens collected in the Río de la Plata basin nested with the remaining specimens, being slightly closer to those from the Guaporé, Napo and Uatumã rivers. Measurements such as caudal peduncle depth, body depth, and body width affected more heavily the first components. Cluster analysis did not show well-defined groups based on the hydrogeographic basins. The studied specimens from the Río de la Plata basin are herein confirmed as conspecific with P. trimaculatus. The species is added to the list of fish species shared between the Amazon and Río de la Plata basins.